Imagine this! doodles to draw out your life purpose - Ramirez, Eduardo Miguel F. (Quezon City Shepherd's Voice Publications, Incorporation, 2016)
Imagine This! is great to use as meeting icebreakers and sharing starters for community gatherings, team building sessions, classroom discussions, and for meaningful conversations with family and friends.
Chapter one: If life doesn't make sense -- Chapter two: If you're searching for your life purpose -- Chapter three: If you wan't to be really happy -- Chapter four: If you don't believe in #forever -- Chapter five: If you're ready to move on -- Chapter six: If your problems are bigger than you -- Chapter seven: If you're scared of the unknown -- Chapter eight: If you're tired of doing the same old routine -- Chapter nine: If you've done your best, but it wasn't good enough -- Chapter ten: If you feel that everyone's successful except you -- Conclusion: if you want to bless the world! -- About the author.
Keywords: Identity (Psychology) -- Religious aspects -- Christianity; Spiritual life -- Christianity; Change -- Religious aspects -- Christianity